Knowledge of traffic law by victims of accidents in belo horizonte, in 1997 - Fagundes-Pereira, Walter J.; Tanure, Raquel; Petroianu, Andy (Medicina (Ribeirao Preto), 1998)
Traffic accidents are one of the great causes of disability and of death mainly in young people of our country. The present study assessed the knowledge of traffic laws of one hundred victims of accidents 67 men and 33 women, in Belo Horizonte, in 1997. Their ages ranged between 18 and 80 (M=36,8 17,2) years old. Only seven of them had drive license and only, other 17 had knowledge about the traffic laws. So 76% of victims do not have knowledge about the traffic laws. We believe that it is worth to suppose people who do not know about traffic laws may be more susceptible to car accidents. The lack of knowledge on basic traffic laws may contribute increasing the amount of accidents.